Ultrasonic Proximity Sensor Device to Enhance the Efficiency of Livestock Transport Process - Arbiyani, Filian (Enthalpy : Jurnal Ilmiah Mahasiswa Teknik Mesin, 2024)
Parking a vehicle is a difficult task for some people and can take a lot of time. This problem is also experienced by the livestock drivers at Farm as the transported animals and feed obstruct their backsight. Moreover, the parking space is limited. Therefore, this research aims to build the Ultrasonic Proximity Sensor device to assist drivers to be more efficient in parking their vehicles and avoid accidents. The research is first carried out by identifying the problems which then continued with the design process and manufacturing the Ultrasonic Proximity Sensor device. After the manufacturing process, the Ultrasonic Proximity Sensor device is tested to ensure that it can display the remaining distance on the LCD and provide warnings through LEDs and buzzers. The results of this research have assisted the drivers, specifically when they are maneuvering backwards, and enhances the efficiency of livestock transport process at Farm.